Interaction Pattern of Groundwater and Surface Water of Beji River in Malang Regency - Fatikasari, Cindi; Siswoyo, Hari; Irawan , Dasapta Erwin (Fakultas Teknik Universitas PGRI Banyuwangi, 2024)
Activities in the Beji River area such as bathing, washing, toilets, industry, and agriculture greatly affect the declinein the quality of the river's. Poor river surface water quality will affect the quality of groundwater in the area around the river.Groundwater and river surface water have a close relationship with each other, especially in areas around riverbanks. Therefore,this study was conducted to identify the interaction between ground air and river surface air at the research location. Based onthe description of the flow pattern identified as a whole, the type of interaction at the research location is in the form of gainstream. The relationship between the two causes similar characteristics as evidenced by the occurrence of similar patterns in thetime series analysis. These similarity characteristics are divided into 2 clusters, namely cluster 1 is influenced by pH and airtemperature while cluster 2 is influenced by TDS and DHL water with correlation values ranging from -0.074 to 0.972. Based onthe PCA analysis, the eigenvalue values obtained range from 1.042 to 1.482 with a cumulative contribution of variables of 79.58%.The hydrochemistry of air in groundwater and river surface water also shows that there are similarities in the chemical propertiesof air, namely that it has non-dominant types of cations and anions.